HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA DENGAN PELAKSANAAN PERAWATAN DI RUMAH PENYAKIT DERMATITIS PADA ANAK DI WILAYAH KERJA PUSKESMAS DESA GEDANG KOTA SUNGAI PENUH TAHUN 2017 - Herlina, Devfi (Menara Ilmu, 2019)
Dermatitites are skin inflammation in the epidermis and dermis in response to the influence of exogenous or endogenous factors that cause clinical symptoms of polymorphic efflorescence (erytma, edema, papules, vesicles, skuama) and itching. The better the knowledge will be good also the implementation of such dermatitis treatment, vice versa if lack of knowledge it will be less in the implementation of dermatitis treatment. This study aims to determine the relationship between the level of knowledge of parents with the implementation of care at home dermatitis disease in children in the working area of village health center gedang full city of 2017. Type of research method Descriptive analytics, the sample size of 67 people with Total Sampling technique. The results showed that there was a significant correlation between the relationship of knowledge level of parents with the implementation of dermatitis disease treatment in children in the Working Area of Puskesmas Desa Gedang Kota Sungai Penuh 2017 with p-value = 0,012 (p <0,05).It is expected that the results of this study can be continued to conduct further research with variables and different places so as to better know the information about the implementation of the treatment of dermatitis disease in children. Keywords: Knowledge, Implementation of dermatitis treatment References: 30 (2003-2017)